Prevalence of autism spectrum disorder symptomatology and related behavioural characteristics in individuals with Down syndrome. (July 2013) - Moss, Jo; Richards, Caroline; Nelson, Lisa; Oliver, Chris
We evaluated the proportion of individuals with Down syndrome (DS: N = 108) who met criteria for autism spectrum disorder (ASD) on the Social Communication Questionnaire and the severity of ASD-related symptomatology in this group. The proportions of individuals with DS meeting the cut-off for ASD and autism in this sample were 19% and 8%, respectively. We then evaluated the behavioural profile of individuals with DS who scored above cut-off for ASD (DS+ASD; N = 17) compared with those with DS-only (N = 17) and individuals with idiopathic ASD (N = 17), matched for adaptive behaviour skills and ASD symptom severity (ASD group only). Individuals in the DS+ASD and ASD-only groups showed more stereotyped behaviour, repetitive language, overactivity and self-injury than the DS-only group (p < .001). Individuals in the DS+ASD and DS-only groups appeared less withdrawn from their surroundings than those with ASD (p < .004). These findings indicate differences in the behavioural and cognitive profile of individuals with DS+ASD compared with those with DS-only, when controlling for adaptive behaviour skills. Individuals with DS+ASD show broad similarities with individuals with idiopathic ASD with regard to ASD and behavioural characteristics but may also show some areas of subtle difference from this group.